Pembaruan Etika Profesi Hukum sebagai Upaya Menjaga Independensi Peradilan dan Memenuhi Tuntutan Transparansi Publik: Studi pada Pengadilan Negeri Kudus - Ida rachmawati89 (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Legal professional ethics is a moral and normative foundation for maintaining the integrity and legitimacy of the judiciary. Modern society presents a dilemma between demands for public transparency and the need to safeguard judicial independence. This study examines the renewal of legal professional ethics as a bridge between transparency and independence, focusing on the Kudus District Court. Using a normative juridical approach supported by philosophical and sociological analysis, the findings show that ethics serves dual functions: ensuring public accountability through transparency and protecting judicial independence from external interference. The study concludes that adaptive, contextual, and progressive ethical renewal is essential to balance these interests.